A comprehensive learning of architecture education: understanding critique session as learning process and criteria-based assessment in the architecture design studio - Utaberta, Nangkula; Hassanpour, Badiossadat; Bahar, Mohd Arsyad; Che Ani, Adi Irfan (Elsevier, 2013)
In the educational process, a process of continuous and comprehensive learning becomes very important. This paper has the aim to analyze and evaluate the whole process of teaching methods in architecture studio. This research is an action observation and analysis of the student 2nd year Architecture Design Studio Universiti Kebangsaan Malaysia (UKM) on their learning and assessment process in design studio. In the process of education, the teaching process is very important to determine the final result or assessment. Therefore, the implementation of a comprehensive educational process has a very important function. The teaching process in the architectural education viewed from two aspects, the aspects of teaching and assessment. Both of the aspects are using different learning methods, namely Critique Session and Criteria-Based Assessment. With these methods we have been able to conclude that both methods are holistic approaches and very helpful in the learning process of students as they are gradually and continuously develop their ability in the learning experience in design studio.